Revestimentos de carragenanas adicionadas de cera de carnaúba para conservação pós-colheita de frutas - Braga, Licia Amazonas Calandrini (2016)
Polysaccharide-based edible films have been studied as materials to help food packaging in its protection function. On the other hand, polysaccharides have high water vapor permeability, which compromises some applications, especially in high relative humidity places. The objective of this study was to evaluate effects of different carnauba wax contents on properties of films from a mixture of sea algae polysaccaharides (-carrageenan, -carrageenan, and alginate). Films were produced with three carnaúba wax contents (1.5, 3, and 5%), besides a control (without wax), and had their tensile properties and water vapor permeability studied and compared by means of Tukey and Dunnett tests. Infrared (FTIR) spectra were also studied. The presence of carnauba wax impaired the tensile properties of the films (except for elongation), whereas their barrier to water vapor was improved. The FTIR spectra showed several bands related to the structure of polysaccharides, with slight changes from the presence of carnauba wax